GDP, Wages, Employment, and Demography: What drives the Financing of Health Insurance? Factor Analysis of the German Statutory Health Insurance 1996-2016 - Thomas Neusius (RheinMain University of Applied Sciences, Wiesbaden Institute of Finance and Insurance (wifi), 2018)
For the German statutory health insurance (SHI), the development of health spending and of the contribution relevant income is analyzed between 1996 and 2016 with respect to the relevant economic and demographic driving factors. The analysis allows identification and quantification of the main drivers of the contribution rate (CR) being the percentage of income that has to be paid as contribution to SHI. It turns out that the most dominant driver for an increasing CR is the aging of the insureds. Additionally, the growing employment also had a pushing effect on the CR as the number of contribution paying SHI members did not grow in equal measure. Only a moderate contribution can be ascribed to the reduced growth of the contribution relevant income. – – Die Entwicklung von Leistungsausgaben der GKV und von Einkommen der Mitglieder wird im Zeitverlauf für die Jahre 1996 bis 2016 nach volkswirtschaftlichen und demographischen Einflüssen zerlegt. Dadurch kann identifiziert und quantifiziert werden, welche Effekte verantwortlich waren für die Entwicklung des Beitragssatz der GKV. Es zeigt sich, dass im Zeitraum 1996 bis 2016 v.a. demographische Veränderungen zu einem Anstieg der Leistungsausgaben geführt haben. Ein kleinerer Teil der Beitragssatzdynamik ist dem Absinken der Lohnquote am BIP geschuldet, was die These von einer strukturellen Einnahmeschwäche der GKV relativiert. Ein weiterer beitragssatzsteigernder Effekt ist die trotz ansteigender Erwerbstätigenquote nur langsam steigende Zahl beitragspflichtiger Mitglieder.
Keywords: I13; I15; J11; H51; 330; demography; health insurance; medical inflation; health expenditure